The Sadharanikaran Model of Communication within the Indigenous Knowledge System: An Appraisa - Verma, Kajal; Malik, Pawan (Bodhi: An Interdisciplinary Journal, 2024)
Communication is a very wide and dynamic process involving many more elements than the information exchange like environment, mood, the satisfaction derived, and mutuality. Among Eastern Communication theories and models, the Sadharanikaran Model of Communication by Nirmala Mani Adhikary (2003) is a model based on Hindu communication perspectives. This paper focuses on understanding and reviewing communication from the perspectives of Sadharanikaran Model of Communication. For this, a systematic review has been conducted, including articles, research papers, and book chapters to reflect the information from fundamentals to contemporary scenarios of works concerning Sadharanikaran and Sadharanikaran Model of Communication. This study concludes that SMC must be studied from other angles like its application in different fields and contexts other than the comparative analysis. This model of communication shall be considered as the evergreen model of communication due to its emphasis on the inclusion of non-cognition elements in communication